ENFORCEMENT OF ENVIRONMENTAL LAW IN POLLUTED RIVER BASINS - McLaren, Heaven; Muhammad, Arif Nur; Darma, Rassel Surya (JILPR Journal Indonesia Law and Policy Review, 2025)
River pollution has become a crucial environmental issue in Indonesia, particularly in the Ciliwung River Basin (DAS), which flows through densely populated areas of Jakarta. This research aims to analyze the implementation of environmental law enforcement in polluted river basins in Indonesia, taking the Ciliwung River as a case study, and to identify lessons learned from Japan's success in overcoming river pollution. The research methodology uses a normative juridical and empirical juridical approach, with data collection techniques through literature review and observation. The results show that environmental law enforcement in the Ciliwung River Basin is not yet optimal due to weak inter-agency coordination, minimal community participation, and low implementation of administrative, civil, and criminal legal instruments. Meanwhile, Japan has successfully carried out river restoration through the implementation of comprehensive policies, including environmental law reform, strengthening law enforcement, community participation, and innovation in water management technology. This research recommends strengthening the implementation of Law No. 32 of 2009 concerning Environmental Protection and Management with an integrated approach that combines administrative, civil, and criminal legal instruments, and involves active community participation in efforts to restore the Ciliwung River Basin and other polluted rivers in Indonesia.